Measuring the Effectiveness of Furniture Sample Export via Air Cargo in the Furniture Industry Using Simple Weighting Method - Peni Shoffiyati; Dian Purnomo; Fesa Kristianto (Politeknik APP Jakarta, 2025)
This research aims to improve logistics in Indonesia's furniture export sector, focusing on companies that face challenges in choosing the best air cargo service for product samples. While air cargo is preferred for its speed and reliability, selecting the optimal provider remains complex due to various service factors. The study applies the Simple Additive Weighting (SAW) method to evaluate air cargo services based on six criteria: delivery speed, document preparation, problem handling, customer maintenance, promotional activities, and shipping cost. The results indicate DHL as the best provider with a score of 0.93913, followed by FedEx and TNT Express. DHL excels in delivery speed and document preparation, crucial for international trade. This study highlights the SAW method's effectiveness in offering a transparent, data-driven approach to logistics decision-making, potentially benefiting other companies facing similar logistics challenges, improving shipment efficiency, reducing costs, and enhancing global competitiveness.